On the Morphosyntax of Augmentatives in Brazilian Portuguese - Armelin, Paula Roberta Gabbai (Revista Letras, 2017)
This paper investigates augmentative formation with -ão and -zão in Brazilian Portuguese. The empirical guideline is divided into two main lines: (i) the interaction between augmentative and gender, and (ii) the (im)possibility of a non-compositional interpretation being attributed to the augmentative structure. Assuming a syntactic approach to word formation (Halle and Marantz, 1993; Borer, 2003), this paper proposes that -ão augmentative structure may either show one ore two gender heads. When two gender heads are present in the structure, a mechanism of gender agreement (Chomsky, 2000, 2001) is assumed to be operating within words. Nevertheless, when only one gender head is present, no gender agreement is possible and the resulting augmentative gender is a default masculine. Based on Borer (2013), this paper proposes that elements within the first functional head of the Extended Projection are able to trigger non-compositional reading. This is exactly the case of the -ão formative when only one gender head is present. The differences in the behavior between -ão and -zão are derived from the fact that the gender head that attaches to the augmentative -zão is not optional, and while -ão attaches below a number head, -zão, on the other hand, attaches above a number head. Finally, the impossibility that the -zão augmentative constructions be non-compositionaly interpreted is derived from the fact that there is too much syntactic material intervening between the augmentative head and the root.